Community organization factors affecting veteran participation in adaptive sports. (4th May 2022) - Whiting, Zachariah G.; Falk, David; Lee, Jonathan; Weinman, Beth; Pines, Jesse M.; Lee, Kenneth
Abstract : Objective: This study aims to describe United States military veteran participation in adaptive sports and to assess the demographic make-up and organizational characteristics of existing adaptive sports programs. Design: Prospective, cross-sectional survey. Setting: Community organizations with adaptive sports programs. Participants: 85 adaptive sports programs. Interventions: Nine question survey. Outcome Measures: Demographic data and sports offered by adaptive sports programs in the United States. Results: The survey response rate was 70%. The median number of total participants in an organization was 75 and the median number of veterans was 50. 76% of organizations had some degree of affiliation with a VAMC. Organizations affiliated with a VAMC are more likely to be rehabilitation centers, whereas community organizations with no VAMC affiliation are most commonly independent organizations with no rehabilitation component. Individuals of all ages participate in adaptive sports, with increasing participation associated with increasing age. Golf was the sport offered most commonly by adaptive sports programs in this survey. Low-contact sports were offered more often than high-contact sports, and the majority of programs offered adaptive sports year-round. Conclusions: Our results suggest that U.S. Military veterans represent a large proportion of the individuals participating in adaptive sports. Further research specifically focusing on factors veterans find desirable when considering participating in adaptive sports is indicated to identify programs that should be promoted, developed, and funded to increase veteran participation in adaptive sports.